The state-of-the-art wireless body area sensor networks: A survey. (April 2018) - Khan, Rahat Ali; Pathan, Al-Sakib Khan
Wireless body area sensor network is a sub-field of wireless sensor network. Wireless body area sensor network has come into existence after the development of wireless sensor network reached some level of maturity. This has become possible due to the tremendous technological advancement leading to easy-to-use wireless wearable technologies and electronic components that are small in size. Indeed, this field has gained significant attention in recent time due to its applications which mostly are toward healthcare sector. Today, tiny-sized sensors could be placed on the human body to record various physiological parameters and these sensors are capable of sending data to other devices so that further necessary actions could be taken. Hence, this can be used for diagnosis of disease and for developing serious health-complication alert systems. Considering this recent hot topic, the intent of this work is to present the state-of-the-art of various aspects of wireless body area sensor network, its communication architectures, wireless body area sensor network applications, programming frameworks, security issues, and energy-efficient routing protocols. We have tried to cover the latest advancements with some discussion on the available radio technologies for this type of network. Future visions and challenges in this area are also discussed.